Analisis Perbandingan Kinerja Keuangan Sebelum Dan Sesudah Initial Public Offering (IPO) Pada PT. Bukalapak Tbk - Annisa Melenia; Chairun Amallia; Yuliarni Putri (Fakultas Ekonomi Universitas Andalas, 2023)
This study aims to determine the comparison of the financial performance of liquidity, solvency, activity and profitability before and after being designated as an initial public offering. This research is classified as quantitative research. The object in this research is PT. Bukalapak Tbk. The type of data used in this research is secondary data. The analytical method used is comparative analysis. To test the hypothesis using the paired sample t-test and the Wilcoxon test. The results of this study conclude (1) There is no significant difference in financial performance in terms of liquidity indicators before and after being designated as an initial public offering. (2) There is no significant difference in financial performance seen from the solvency indicators before and after being determined as an initial public offering. (3) There is no significant difference in financial performance seen from the activity indicators before and after being determined as an initial public offering. (4) There is a significant difference in financial performance seen from the profitability indicators before and after being determined as an initial public offering.